2021
DOI: 10.1186/s12883-021-02096-w
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular ejection fraction and right atrial diameter are associated with deep regional CBF in arteriosclerotic cerebral small vessel disease

Abstract: Background Systemic cardiac hypoperfusion is a well-acknowledged contributor to ischemic leukoencephalopathy. However, it has remained elusive how atherosclerosis-mediated cardiac remodelling modifies cerebral perfusion homeostasis as well as neuroimaging burden in cerebral small vessel disease (CSVD) development. Methods This retrospective study identified 103 arteriosclerotic CSVD (aCSVD) patients (CSVD burdenlow 0 ~ 1, n = 61 and CSVD burdenhigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Traditional studies of CSVD have been conducted before determining subtypes on the basis of perfusion patterns, these studies commonly revealed overlapping relationships between CSVD clinical symptoms and CBF ( Chen et al, 2021 , Jann et al, 2021 , Yu et al, 2020 ). In the current study, associations between clinical symptoms and CSVD were assessed after determining the CSVD subtypes, and several common risk factors between healthy controls and CSVD patients were found, including age, proportion of subjects drinking alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional studies of CSVD have been conducted before determining subtypes on the basis of perfusion patterns, these studies commonly revealed overlapping relationships between CSVD clinical symptoms and CBF ( Chen et al, 2021 , Jann et al, 2021 , Yu et al, 2020 ). In the current study, associations between clinical symptoms and CSVD were assessed after determining the CSVD subtypes, and several common risk factors between healthy controls and CSVD patients were found, including age, proportion of subjects drinking alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…According to one study (22) of chronic valvular heart disease patients, right atrial pressure is independently associated with higher WMH volume. RAD has also been reported (23) to be negatively correlated with mean deep regional CBF. Collectively, there is therefore a need to continuously pay attention to pathogenesis involving RAD in CSVD in future research.…”
Section: Discussionmentioning
confidence: 86%
“…This suggests that periventricular CBF could be an early biomarker of cSVD. In another study, echocardiographic and deep regional CBF in arteriosclerotic cSVD showed association with total burden, suggesting a prognostic potential 29 . Also, a correlation was found between thalamic blood flow measured with ASL and gait in an elderly group with at least one vascular risk factor, suggesting that subcortical vascularity must be considered when studying the functional decline in the elderly population 30 …”
Section: Resultsmentioning
confidence: 96%
“…In another study, echocardiographic and deep regional CBF in arteriosclerotic cSVD showed association with total burden, suggesting a prognostic potential. 29 Also, a correlation was found between thalamic blood flow measured with ASL and gait in an elderly group with at least one vascular risk factor, suggesting that subcortical vascularity must be considered when studying the functional decline in the elderly population. 30 Finally, an ASL pulse sequence combined with diffusion gradients before the readout module (DP-pCASL, diffusion-prepared pCASL) appears to be a promising approach to noninvasively map the water exchange across the BBB.…”
Section: Asl: Csvd and Cbf Deregulationmentioning
confidence: 95%